Sicily : an island at the crossroads of history - Norwich, John Julius, 1929-2018 (Random House, 2015)
"'Sicily,' said Goethe, 'is the key to everything.' The birthplace of Archimedes, Georgio de Chirico, and Muhammad al-Idrisi, it is the largest island in the Mediterranean. The stepping-stone between Europe and Africa, the gateway between the East and the West, the link between the Latin world and the Greek, at once a stronghold, clearing-house and observation-point, it has been fought over and occupied in turn by all the great powers that have striven over the centuries to extend their dominion across the Middle Sea. John Julius Norwich offers a vivid, erudite, page-turning account of an island and the remarkable kings, queens, and tyrants who fought to rule it. From its beginnings as a feared Greek city-state to its rise as a wealthy, multicultural trading hub during the Crusades, to its rebellion against Italian unification and the rise of the Mafia, the story of Sicily is rich with extraordinary moments and dramatic characters. Norwich outlines the surprising influence Sicily has had on world history--the Roman fascination with Greek culture dates back to their sack of Sicily--and tells the story of one of the world's most kaleidoscopic cultures in a galvanizing, contemporary way"--